EFEK SIKAT GIGI KONVENSIONAL DAN SIKAT GIGI KHUSUS ORTODONTI DALAM PENURUNAN INDEKS PLAK PASIEN ORTODONTI PIRANTI CEKAT: EFFECT OF CONVENTIONAL TOOTH BRUSH AND SPECIFIC ORTHODONTIC TOOTH BRUSH TO DECREASE PLAQUE INDEX OF FIXED ORTHODONTIC PATIENTS - Wirna Sukmawaty; Simson Damanik (Dentika: Dental Journal, 2011)
Orthodontic toothbrush designed specifically to eliminate plaque around brackets, but there are still many patient who use conventional toothbrush. This study aimed to know the effect of an orthodontic toothbrush compare to a conventional toothbrush in reducing plaque index. The plaque index used was a modification of patient hygiene performance (PHP) index developed by Podshadley and Haley. The design of this study was a pre and posttest experimental design. Sample consist of 80 students of dental faculty. The results of the t- test statistical analysis s howed that there was a significant difference of reduction plaque index from 2.96 to 2.07 (p <0.05). It can be concluded that a specific orthodontictoothbrush has a better role to reduce the plaque index than a conventional toothbrush.